The testament of Jesus a study of the gospel of John in the light of chapter 17 - Kasemann, Ernst; Krodel, Gerhard (London, UK SCM, 1968)
Includes bibliographical references and indexes.
Originally published "Jesu letzter Wille nach Johannes 17", Tubingen, J.C.B. Mohr (Paul Siebeck), 1966.
Keywords: Bible. N.T. John -- criticism, interpretation, etc; Bible. N.T. John XVII, -- criticism, interpretation, etc